Applications of MALDI mass spectrometry imaging for pharmacokinetic studies during drug development - Nishidate, Masanobu; Hayashi, Mitsuhiro; Aikawa, Hiroaki; Tanaka, Kouji; Nakada, Naoyuki; Miura, Shin-ichi; Ryu, Shoraku; Higashi, Tatsuya; Ikarashi, Yoshinori; Fujiwara, Yasuhiro; Hamada, Akinobu (Drug metabolism and pharmacokinetics, 2019)
The concentration and distribution of a drug or its metabolites in tissues are key factors for understanding drug efficacy or toxicity. Conventional pharmacokinetic studies show that the plasma concentration of a drug is often unrelated to the intra-tissue concentration. Moreover, it is difficult to predict the distribution of a drug in tissues, particularly those with complex structures, even though the overall tissue concentration is measured by using homogenizing procedures. Mass spectrometry imaging (MSI) enables visualization of the spatial distribution and quantities of drugs in tissue sections without labeling, which can significantly impact on the development of new drugs and translational research. Recent advances in instrument technology and the knowledge accumulated to date could further improve the sensitivity, spatial resolution, and reproducibility of MSI. Here we present current applications of matrix-assisted laser desorption/ionization (MALDI)-MSI in pharmacokinetic imaging (PK-imaging) studies, give an overview of MALDI-MSI procedures, highlight the importance of internal standards, and give details of quantitative approaches. We also point out the need for standardizing MALDI-MSI techniques. PK-imaging using standardized MALDI-MSI methods, independent of instrument or technician expertise, is expected to contribute to acquiring reliable data in drug development and translational research in the future. [Display omitted]